Performance of a prediction method for activities of daily living scores using influence coefficients in patients with stroke - Kobayashi, Ryu; Kobayashi, Norikazu (Frontiers in Neurology, 2024)
Introduction Recently, a method was developed to predict the motor Functional Independence Measure (FIM) score at discharge in patients with stroke by stratifying the effects of factors such as age and cognitive function and multiplying those by the influence coefficients of these factors. However, an evaluation of the predictive performance of the method is required for clinical application. The present study aimed to evaluate the predictive performance of this prediction method. Methods Patients with stroke discharged from a rehabilitation ward between April 2021 and September 2022 were included. Predicted values of the motor FIM score at discharge were calculated after data collection from the hospital’s patient database. The concordance between predicted and actual values was evaluated using the interclass correlation coefficient; moreover, the residual values were calculated. Results In total, 207 patients were included in the analysis. The median age was 79 (69–85) years, and 112 (54.1%) patients were male. The interclass correlation coefficient between predicted and actual values was 0.84 (95% confidence interval 0.75–0.89) for the motor FIM score at discharge. Meanwhile, the median residual value was 5.3 (−2.0–10.3) for the motor FIM score at discharge. Discussion The prediction method was validated with good performance. However, the residual values indicated that some cases deviated from the prediction. In future studies, it will be necessary to improve the predictive performance of the method by clarifying the characteristics of cases that deviate from the prediction.